Agricultural Entrepreneurship Motivation Policies: European Union Experience and Decision Theory Application. (April 2019) - Dobryagina, Natalia
The European Union (EU) policies devoted to entrepreneurship in agricultural motivation represent a wide spectrum of methods and approaches. However, lack of attention to the differences between different types of entrepreneurs might decrease the entrepreneurship motivation policies' effectiveness. Applying Decision Theory (DT), one of the management sciences, the article determines that non-hereditary entrepreneurs, which include ex novo and early retirement groups, are expected to provide greater contribution to the rural areas development and have different decision-making process in contrast to hereditary entrepreneurs. The article clearly shows a lack of policies focused on non-hereditary entrepreneurs in the EU and a limited effect of policies on ex novo and early retirement groups due to their underestimation of the agricultural sphere's opportunities and limited knowledge about existing policies. The article suggests further application of DT in agricultural entrepreneur's motivation and debiasing.